Incontinentia pigmenti with seizure and deafness. - Fabrizi, G.; Agnusdei, C.P.; Nowak, J.; Pagliarello, C. (European Journal of Pediatric Dermatology, 2007)
A case of incontinentia pigmenti with the typical lesions of the neonatal period, seizure and deafness is reported.